East of Nicaea: Trinitarian Orthodoxy and Its Early Adoption in Unexpected Territory - Doerfler, Maria E. (Religion & theology, 2025)
A commonly asserted dogma of Nicene reception has been the creed’s early and enthusiastic incorporation into the theology of Syriac Christianity’s most famous representative, Ephrem of Nisibis. The latter’s oeuvre indeed directs considerable intellectual firepower against those that sought to subordinate the Son to the Father. Recent scholarship, however, has noted Ephrem’s own ambivalence about aspects of the Nicene Creed, including the famous "homoousios." This article considers the evidence of the so-called "Hymns on Nisibis" (Carmina Nisibena), in light of the apparent schism between subordinationists and pro-Nicenes in Edessa. The Hymns showcase Ephrem’s theological commitments to be consistent with those of his other work, most notably the Hymns on Faith, while providing glimpses at his efforts to effect reconciliation among Edessene Christians - even at the risk of valorizing aspects of opposing factions’ views.